2005
DOI: 10.1209/epl/i2005-10039-9
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nanoscale pore arrays during anodization of aluminum

Abstract: Abstract. -A theory of the spontaneous formation of spatially regular hexagonal arrays of nanopores in aluminum oxide film growing during aluminum anodization is presented. Linear stability analysis shows that, in certain ranges of the applied voltage and electrolyte pH, the oxide film is unstable with respect to perturbations with a well-defined wavelength. The instability is caused by a positive feedback between the oxidation-dissolution rates and variations of electric field caused by perturbations of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 28 publications
1
51
0
Order By: Relevance
“…At 20 V we see that the pores vary widely in diameter and they are not very well organized into rows. This disorder in pore growth was shown to be an unstable configuration in the papers by Singh et al 5,6 We can see that as the voltage increases, the pores become more ordered. At about 100 V the pores become fairly uniform in diameter and also self-organize themselves evenly.…”
Section: Experimental Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…At 20 V we see that the pores vary widely in diameter and they are not very well organized into rows. This disorder in pore growth was shown to be an unstable configuration in the papers by Singh et al 5,6 We can see that as the voltage increases, the pores become more ordered. At about 100 V the pores become fairly uniform in diameter and also self-organize themselves evenly.…”
Section: Experimental Methodsmentioning
confidence: 74%
“…But, their model does not account for dependence of morphology on the applied voltage. Perhaps the most successful model was published recently by Singh et al 5,6 In their model, the authors began from the same first principles as Parkhutik and Shershulsky, but note that there are various growth regimes which depend on the voltage. Also, they note definite instabilities in the growth mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of stress effects, the system can only yield long-wave instabilities which usually lead to the growth of irregular arrays of pores seen in other oxide materials such as titanium as well as AAO for certain parameter regimes [31,32]. Taking typical electrochemical [43,42,41,15,44], electrostrictive [38] and elastic [45,46,44,47] parameter values, we numerically obtain the roots of Eq.…”
Section: Resultsmentioning
confidence: 99%
“…In [29], the effects of interfacial diffusion at the metal-oxide interface were investigated, and in [30], the effects of a field-dependent oxide conductivity were explored. The model proposed by Singh et al in [31,32] included the contributions of elastic stress to the surface activation energies, and it was shown that these effects can result in a short-wave instability which can explain the formation of hexagonally ordered pores. The validity of this model was explored experimentally in [33,34,35,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation